Signal crayfish burrowing, bank retreat and sediment supply to rivers: A biophysical sediment budget. Issue 4 (5th February 2021) - Sanders, H.; Rice, S.P.; Wood, P.J.
Abstract: Burrowing into riverbanks by animals transfers sediment directly into river channels and has been hypothesised to accelerate bank erosion and promote mass failure. A field monitoring study on two UK rivers invaded by signal crayfish ( Pacifastacus leniusculus ) assessed the impact of burrowing on bank erosion processes. Erosion pins were installed in 17 riverbanks across a gradient of crayfish burrow densities and monitored for 22 months. Bank retreat increased significantly with crayfish burrow density. At the bank scale (<6 m river length), high crayfish burrow densities were associated with accelerated bank retreat of up to 253% and more than a doubling of the area of bank collapse compared with banks without burrows. Direct sediment supply by burrowing activity contributed 0.2% and 0.6% of total sediment at the reach (1.1 km) and local bank (<6 m) scales. However, accelerated bank retreat caused by burrows contributed 12.2% and 29.8% of the total sediment supply at the reach and bank scales. Together, burrowing and the associated acceleration of retreat and collapse supplied an additional 25.4 t km −1 a −1 of floodplain sediments at one site, demonstrating the substantial impact that signal crayfish can have on fine sediment supply. For the first time, an empirical relation linking animal burrow characteristics to riverbank retreat is presented. The study adds to a small number of sediment budget studies that compare sediment fluxes driven by biotic and abiotic energy but is unique in isolating and measuring the substantial interactive effect of the acceleration of abiotic bank erosion facilitated by biotic activity. Biotic energy expended through burrowing represents an energy surcharge to the river system that can augment sediment erosion by geophysical mechanisms. Abstract : Riverbank burrowing by animals supplies sediment directly into river systems and has been hypothesised to increase bank erosion and promote mass failure. This field study of two rivers invaded by signal crayfish examines the rates and mechanisms of bank retreat under increasing densities of crayfish burrows and quantifies a sediment budget that partitions biotic, abiotic and interactive processes in driving fine sediment recruitment to river systems.